Patriachy to Modernism: Real or Circumstantial (with special reference to Mahesh Dattani’s Dance Like a Man) - Mehdi, Zeba; Kumar, Shravan (International Journal of Psychosocial Rehabilitation, 2020)
The present paper intends to highlight the transgression from patriarchal system to modern thoughts. Dattani brings a ray of hope for all the suppressed classes that every person has his day. The work aims at discussing the deep roots of the traditional norms that gradually seem to be changing but the fear remains as the change be circumstantial alone. The main purpose of the paper is to bring into light the arbitrary rule of a man in the house and its acceptance even by the second generation. The third generation seems to be relaxed and follows its own will. The paper targets the suppression of the views of the mrginalised. Dattani depicts how a rebellious couple accepts the patriarchal win. In fact, the present paper demonstrates the circumstantial changes in the attitude of the people. The work does not claim the change has definitely been accepted by the patriarchs but sometimes many reasons altogether bring about a new change.